Egg quality and carcass characteristics of Nag Hans – A local duck in Bastar region of Chhattisgarh - MESHRAM, DEVESH; PARVEEN, KAISER; MUKHERJEE, K; BARWA, DEEPTI KIRAN (The Indian Journal of Animal Sciences, 2025)
The present study was carried out to study egg quality and carcass characteristics of Nag Hans, a local duck of Bastar region in Chhattisgarh. About 300 eggs were examined to study the internal and external egg quality and 20 birds (10 male and 10 female) were slaughtered to study carcass characteristics. All the statistical analyses were done using R statistical software 2020. The different egg quality traits egg weight (g), shell weight (g), albumen weight (g), yolk weight (g), shell thickness (mm), specific gravity, albumen index, Haugh unit and yolk index recorded were 57.45±0.54, 6.57±0.09, 23.21±0.15, 24.70±0.31, 0.36±0.03, 1.15±0.09, 22.69±10.35, 89.52±1.14 and 40.04±0.39 respectively. The different carcass characters such as age at slaughter (yr), slaughter weight (kg), dressing (%) and meat bone ratio recorded were 1.7±0.12, 2.09±0.18, 73.36±2.71 and 3.81±0.33 respectively for male ducks and 1.34±0.18, 1.25±0.08, 69.21±0.87 and 1.16 for female ducks respectively.